Transcultural Modernisms - House Research Group, Model; Egermann, Eva; Krameritsch, Jakob; Kravagna, Christian; Linortner, Christina; Osten, Marion von; Amir, Fahim; Hille, Moira; Spillmann, Peter (Publication Series of the Academy of Fine Arts Vienna, 2013)
Transcultural Modernisms is based on the findings of an interdisciplinary research project with focus on modernist architectural projects realized in the era of decolonization. It maps out the network of encounters, transnational influences, and local appropriations of an architectural modernity manifested in various ways in housing projects in India, Israel, Morocco, and China that served as exemplary standard models, not only for Western societies. The emphasis in Transcultural Modernisms is on the exchanges and interrelations among international and local actors and concepts, a perspective in which "modernity" is not passively received, but is a concept in circulation, moving in several different directions at once, subject to constant renegotiation and reinterpretation. Modernism is not presented as a universalist and/or European project, but as marked by cultural transfers and their global localization and translation.